Thyroid Function Abnormalities among Hospital Patients of Hilly Nepal - Dangol, Raj Krishna; Lanjekar, Priya; Pulipati, Chandrasekhar (Journal of Lumbini Medical College, 2017)
Introduction: Thyroid dysfunction stands as the second most common endocrine disease after diabetes mellitus. National reports on its prevalence are meagre. Hence, the study was conducted with the objective of exploring the prevalence of thyroid dysfunction among hospital patients of hilly region of Nepal. Methods: A hospital based, retrospective, analytical study was conducted in the department of biochemistry, Lumbini Medical College Teaching Hospital (LMCTH) from 15th February 2017 to 30th April 2017. The hospital records of patients from March 2014 to mid-February 2017 with suspected thyroid dysfunction and presented from different departments of hospital were reviewed. Data was entered in Excel 2007 and analysis was done with Statistical Package for Social Sciences (SPSS-21). Necessary descriptive and inferential statistical analysis was done. P value less than 0.05 was regarded as statistically significant. Results: Out of 3136 subjects, 601 (19.2%) were male and 2535 (80.8%) were female with F:M ratio of 4.2:1. Female were more likely to be suspected of thyroid dysfunction. Mean age of male was 39.28 years (SD = 19.01) and that of female was 39.60 years (SD = 14.63). Prevalence of thyroid dysfunction was 23.31%. Correlation of log10 TSH with age showed a significant relation (r = -0.05, p = 0.003). Age group and thyroid function category among female patients was found to be statistically significant (p = 0.01). Conclusion: The prevalence of thyroid dysfunction was high in Tansen region, a hilly mid-west Nepal. Female above 40 yrs (post reproductive age) and male above 60 yrs (elderly group) were more prone to thyroid disorders. Also, the study revealed that younger people are more likely to be euthyroid whereas as age advances, people are likely to be either hypothyroid or hyperthyroid. These findings can be a guide for elaborative research in thyroid disorder in future. Journal of Lumbini medical College Vol 5, No 1, Jan-June 2017 Pages 29-33 DOI: https://doi.org/10.22502/jlmc.v5i1.118